Analysis of morbidity and health care usage of patients with suspected thyroid disorders - Tomandl, Johanna; Hafner, Lucas; Biermann, Valeria; Tauchmann, Harald; Schöffski, Oliver; Kühlein, Thomas; Hueber, Susann (Preventing Overdiagnosis Congress 2019, 2019)
Objectives (150 words) In many countries the incidence of thyroid cancer increased in the last years, while thyroid cancer mortality remained stable. This is seen as an indicator for overdiagnosis. Furthermore, many surgically removed thyroid nodules turn out to be benign, especially in Germany. Germany has a highly fragmented health care system with easy access to diagnostic imaging even at the level of general practice. Most thyroid nodules are detected using sonography early in the work-up of suspected thyroid disorders, which might trigger control loops and invasive treatment. Thus, the objective of this study is to systematically analyze whether the early use of sonography in the work-up of suspected thyroid disease might lead in a cascade effect from overdiagnosis to overtreatment. The following research question will be answered: What effects does the early use of sonography in the diagnostic process of suspected thyroid disorders have on morbidity, health care utilization and costs? Method (150 words) To answer this research question a retrospective cohort-study design comparing two propensity-matched groups was chosen. Claims data of patients with statutory health insurance held by the Bavarian Association of Statutory Health Insurance Physicians were used. Early use of sonography was defined as having an initial TSH test followed by a sonography within 28 days. Patients having received a TSH test in 2012 were included and allocated to one of the two following groups: Group 1: TSH test followed by sonography of the thyroid within 28 days. Group 2: TSH test without sonography of the thyroid within 28 days. The two groups were matched for sociodemographic characteristics, morbidity, and reason for encounter using propensity score matching. The two groups are currently compared in terms of morbidity, health care utilization and costs. Results (150 words) After propensity score matching, the sample consisted of 68,862 patients in each group. Data analysis is not completed yet. The results will be available for presentation until the conference. Conclusions (150 words) Early use of sonography in the work-up of suspected thyroid disorders might trigger a cascade of overdiagnosis and overtreatment. By systematically analyzing clinical pathways of patients with suspected thyroid disorders and the resulting medical and economic consequences, we hope to contribute to the identification and reduction of overdiagnosis and overtreatment concerning thyroid disorders. The project is embedded in the PRevention of Overdiagnosis in PRImary CARE (PRO PRICARE) research network funded by the German Federal Ministry of Research and Education. </

Does Moderate Weight Loss Affect Subjective Health Perception in Obese Individuals? Evidence from Field Experimental Data - Hafner, Lucas; Tauchmann, Harald; Wübker, A. (2017)
This paper analyzes whether moderate weight reduction improves subjective health perception in obese individuals. To cure possible endogeneity bias in the regression analysis, we use randomized monetary weight loss incentives as instrument for weight change. In contrast to related earlier work that also employed instrumental variables estimation, identification does not rely on long-term, between-individuals weight variation, but on short-term, within-individual weight variation. This allows for identifying short-term effects of moderate reductions in body weight on subjective health. In qualitative terms, our results are in line with previous findings pointing to weight loss in obese individuals resulting in improved subjective health. Yet, in contrast to these, we establish genuine short-term effects. This finding may encourage obese individuals in their weight loss attempts, since they are likely to be immediately rewarded for their efforts by subjective health improvments
Keywords: self-rated health; BMI; obesity; randomized experiment; short-term effect; instrumental variable

Does moderate weight loss affect subjective health perception in obese individuals? Evidence from field experimental data - Hafner, Lucas; Tauchmann, Harald; Wübker, Ansgar (Empirical Economics, 2021)
This paper analyzes whether moderate weight reduction improves subjective health perception in obese individuals. Besides simple regression models, in a simultaneous equation framework we use randomized monetary weight loss incentives as instrument for weight change, to address possible endogeneity bias. In contrast to related earlier work that also employed instrumental variables estimation, identification does not rely on long-term, between-individuals weight variation, but on short-term, within-individual weight variation. Yet, our result does not suggest that the simple regressions suffer from much endogeneity bias, since instrumental variables estimation yields similar—though far noisily estimated and statistically insignificant—estimates. In qualitative terms, our results do not contradict previous findings pointing to weight loss in obese individuals resulting in improved subjective health. Our results suggest that a reduction of body weight by one BMI unit is associated with an increase in the probability of reporting self-rated health to be ‘satisfactory’ or better by 3 to 4 percentage points. This finding may encourage obese individuals in their weight loss attempts, since they are likely to be immediately rewarded for their efforts by subjective health improvements.<br
Keywords: self-rated health; BMI; obesity; randomized experiment; short-term effect; instrumental variable; gender

Do minimum wages improve self-rated health? Evidence from a natural experiment - Hafner, Lucas; Lochner, Benjamin (Empirical Economics, 2021)
We analyze whether the introduction of the general minimum wage in Germany in 2015 had an effect on workers’ self-rated health. To this end, we use survey data linked to administrative employment records and apply difference-in-differences regressions combined with propensity score matching. This approach enables us to control for a vast set of potential confounding variables. We find a health improving effect among the individuals who were most likely to be affected by the reform. Our results indicate that workers’ improved satisfaction with pay, their reduced working hours, and a reduction in time pressure at work may drive this resul
Keywords: Minimum wage; self-rated health; natural experiment

In sickness and in health? Health shocks and relationship breakdown: Empirical evidence from Germany - Bünnings, Christian; Hafner, Lucas; Reif, Simon; Tauchmann, Harald (Journal of Economic Behavior & Organization, 2021)
From an economic perspective, marriage and long-term partnership can be seen as a risk-pooling device. This informal insurance contract is, however, not fully enforceable. Each partner is free to leave when his or her support is needed in case of an adverse life event. An adverse health shock is a prominent example for such events. Since relationship breakdown itself is an extremely stressful experience, partnership may backfire as informal insurance against health risks, if health shocks increase the likelihood of relationship breakdown. We address this question empirically, using survey data from Germany. Results from various matching estimators indicate that adverse shocks to mental health substantially increase the probability of a couple splitting up over the following two years. In contrast, there is little effect of a sharp decrease in physical health on relationship stability. If at all, physical health shocks that hit both partners simultaneously stabilize a relationship. </
Keywords: Separation; Partnership dissolution; Health shock; MCS; PCS; Matching; Gender

In sickness and in health? Health shocks and relationship breakdown: Empirical evidence from Germany - Bünnings, Christian; Hafner, Lucas; Reif, Simon; Tauchmann, Harald (Journal of Economic Behavior & Organization, 2021)
From an economic perspective, marriage and long-term partnership can be seen as a risk-pooling device. This informal insurance contract is, however, not fully enforceable. Each partner is free to leave when his or her support is needed in case of an adverse life event. An adverse health shock is a prominent example for such events. Since relationship breakdown itself is an extremely stressful experience, partnership may backfire as informal insurance against health risks, if health shocks increase the likelihood of relationship breakdown. We address this question empirically, using survey data from Germany. Results from various matching estimators indicate that adverse shocks to mental health substantially increase the probability of a couple splitting up over the following two years. In contrast, there is little effect of a sharp decrease in physical health on relationship stability. If at all, physical health shocks that hit both partners simultaneously stabilize a relationship.
CRIS-Team Scopus Importer:2021-09-24
Keywords: Health shock; Matching; MCS; Partnership dissolution; PCS; Separation

In Sickness an in Health? Health Shocks and Relationship Breakdown: Empirical Evidence from Germany - Bünnings, Christian; Hafner, Lucas; Reif, Simon; Tauchmann, Harald (2019)
From an economic perspective, marriage and long-term partnership can be seen as a risk-pooling device. This informal insurance contract is, however, not fully enforceable. Each partner is free to leave when his or her support is needed in case of an adverse life event. An adverse health shock is a prominent example for such events. Since relationship breakdown itself is an extremely stressful experience, partnership may backfire as informal insurance against health risks, if health shocks increase the likelihood of relationship breakdown. We address this question empirically, using survey data from Germany. Results from various matching estimators indicate that adverse shocks to mental health substantially increase the probability of a couple splitting up over the following two years. In contrast, there is little effect of a sharp decrease in physical health on relationship stability. If at all, physical health shocks that hit both partners simultaneously stabilize a relationship.<br
Keywords: separation; partnership dissolution; health shock; MCS; PCS; matching

Kosteneffekte durch nicht indizierte Diagnostik der Schilddrüse - Hafner, Lucas; Tomandl, Johanna; Biermann, Valeria; Tauchmann, Harald; Schöffski, Oliver; Hoyer, Stefanie; Hueber, Susann; Donnachie, Ewan; Kühlein, Thomas (Deutsche Gesellschaft für Gesundheitsökonomie 11. Jahrestagung Gesundheitsverhalten und Prävention, 2019)
Einleitung Die Inzidenz von Schilddrüsenkarzinomen ist bei konstanter Mortalität in jüngerer Vergangenheit in Deutschland stark angestiegen. Dies ist vermutlich auf verbesserte Diagnosemöglichkeiten, die zur Entdeckung zahlreicher kleiner Schilddrüsenknoten führt, die unerkannt nie als medizinisches Problem in Erscheinung getreten wären. Wir untersuchen, ob nicht indizierte Diagnostik im Schilddrüsenkontext zu invasiven Behandlungen und infolge dessen hohen Kosten führt. Konkret untersuchen wir, ob sich durch eine nicht indizierte Sonographie der Schilddrüse die ambulanten, stationären sowie pharmazeutischen Gesundheitskosten bei den betroffenen Patienten kurz und langfristig erhöhen. Methoden Auf Basis von Routinedaten aus Deutschland werden Gesundheitskostenverläufe von Patienten untersucht, deren Symptomatik zu Beginn der Studie auf eine Fehlfunktion der Schilddrüse hindeuten. Bei allen betrachteten Patienten wurde zunächst per Blutuntersuchung der TSH-Wert bestimmt, mit dessen Hilfe Anomalien der Schilddrüsenfunktion identifiziert werden können. Als Interventionsgruppe werden die Patienten betrachtet, bei denen nicht leitliniengerecht, d.h. mit nur kurzem zeitlichen Abstand, zusätzlich eine Sonographie der Schilddrüse durchgeführt wird. Als Kontrollgruppe gelten Patienten ohne oder mit leitlinienkonformer Sonographie. Um mögliche Kosteneffekte der nicht leitliniengerechten Sonographie messen zu können, wird mittels eines Matching-Verfahren sichergestellt, dass sich beide Gruppen hinsichtlich Alter, Geschlecht, Wohnort, ambulantem Behandlungsanlass sowie Morbidität nicht unterscheiden. Ergebnisse Die durchschnittlichen Kosten für schilddrüsenspezifische ambulante Leistungen sowie schilddrüsenspezifische Arzneimittel sind in der Interventionsgruppe signifikant höher als in der Kontrollgruppe. Dieser Unterschied ist auch noch mehrere Jahre nach der Intervention zu beobachten. Allerdings ist der Anteil der schilddrüsenspezifischen Kosten an den Gesamtkosten in beiden Gruppen sehr gering. Hinsichtlich der durchschnittlichen Gesamtkosten (ambulant, stationär und pharmazeutisch) zeigen sich im Analysezeitraum keine signifikant unterschiedlichen Verläufe bei Interventions- und Kontrollgruppe. Fazit Unsere Ergebnisse liefern keine Evidenz dafür, dass eine nicht indizierte Sonographie der Schilddrüse Behandlungskaskaden auslöst, welche zu hohen allgemeinen Gesundheitskosten führt. Lediglich schilddrüsenspezifische Kosten sind nach der nicht indizierten Diagnostik selbst langfristig höher. Im Hinblick auf die Gesamtkosten fällt dieser Kostenunterschied allerdings nicht ins Gewich
Keywords: Gesundheitsökonomische Evaluation; Medizinische Überversorgung; Schilddrüsenerkrankungen

Morbidität und Inanspruchnahme des Gesundheitswesens von PatientInnen mit Verdacht auf Schilddrüsenerkrankungen. Eine retrospektive Kohortenanalyse unter Verwendung von Routinedaten. - Tomandl, Johanna; Hafner, Lucas; Biermann, Valeria; Tauchmann, Harald; Schöffski, Oliver; Hueber, Susann; Kühlein, Thomas (18. Deutscher Kongress für Versorgungsforschung, 2019)
Hintergrund In zahlreichen Ländern ist die Inzidenz von Schilddrüsenkarzinomen bei gleichbleibender Mortalität in den letzten Jahren rasant angestiegen. Dies wird als ein Indiz für Überdiagnostik gesehen. Die Entdeckung von Schilddrüsenknoten erfolgt häufig im Rahmen initial nicht indizierter Diagnostik, die dann Auslöser von Kontrollschleifen und letztlich invasiven Behandlungen sein kann. Gerade in Deutschland gibt es eine hohe Anzahl von Schilddrüsenoperationen, bei denen sich die entfernten Knoten in der anschließenden Histologie häufig als benigne herausstellen. Ziel unsere Studie ist die systematische Analyse, ob der frühzeitige Einsatz der Sonographie im Abklärungsprozess bei Verdacht auf Schilddrüsenerkrankungen in einer Art Kaskade von Überdiagnostik hin zu Übertherapie führt. Fragestellung Welche Auswirkungen hat der frühzeitige Einsatz der Schilddrüsen-Sonographie zur Abklärung von Schilddrüsenerkrankungen auf Morbidität und Inanspruchnahme des Gesundheitswesens bei den betroffenen PatientInnen? Methode Zur Beantwortung der Forschungsfrage wird aktuell eine retrospektive Kohortenanalyse mit Daten der Kassenärztlichen Vereinigung Bayerns (2012 bis 2017) durchgeführt. Untersucht werden Daten von PatientInnen mit und ohne nicht-indizierter Schilddrüsen-Sonographie. Nicht-indizierte Schilddrüsen-Sonographie wird definiert als erstmaliger TSH-Test gefolgt von einem Ultraschall der Schilddrüse innerhalb von 28 Tagen ohne Vorliegen einer Hypo- oder Hyperthyreose. Die beiden Gruppen wurden mittels Propensity Score Matching gematcht und bezüglich Morbidität und Inanspruchnahme des Gesundheitswesens untersucht. Ergebnisse Es werden Daten von 68.862 PatientInnen in jeder Gruppe ausgewertet. Die Datenanalyse ist noch nicht abgeschlossen. Die Ergebnisse werden zum Kongress vorliegen. Diskussion und praktische Implikationen Ein systematischer Vergleich verschiedener Behandlungspfade sowie deren medizinischer und ökonomischer Konsequenzen soll dazu beitragen, Überdiagnostik und Übertherapie zu identifizieren und zu beschreiben. Das Projekt wird im Rahmen des BMBF-geförderten Netzwerkes PRO PRICARE durchgeführt.
Keywords: Überversorgung; Schilddrüsenerkrankungen; Versorgungsforschung; Routinedaten; Kohortenanalyse

Physician behavior under prospective payment schemes: Evidence from artefactual field and lab experiments - Hafner, Lucas; Reif, Simon; Seebauer, Michael (2017)
Recent experimental studies analyze the behavior of physicians towards patients and find that physicians care for their own profit as well as patient benefit. In this paper, we extend the experimental analysis of the physician decision problem by adding a third party representing the health insurance which finances medical service provision. Our results show that physicians take into account the payoffs of the third party, which can lead to underprovision of medical services. We conduct a laboratory experiment in neutral as well as medical framing using students and medical doctors as subjects. Subjects in the medically framed experiments behave weakly more patient orientated in contrast to neutral framing. A sample of medical doctors exhibits comparable behavior to students with medical framing.<br
Keywords: health economic experiment; framing; physician behavior; prospective payment schemes

Physician behavior under prospective payment schemes—evidence from artefactual field and lab experiments - Reif, Simon; Hafner, Lucas; Seebauer, Michael (International Journal of Environmental Research and Public Health, 2020)
Recent experimental studies analyze the behavior of physicians towards patients and find that physicians care for their own profit as well as patient benefit. In this paper, we extend the experimental analysis of the physician decision problem by adding a third party which represents the health insurance that finances medical service provision under a prospective payment scheme. Our results show that physicians take into account the payoffs of the third party, which can lead to underprovision of medical care. We conduct a laboratory experiment in neutral as well as in medical framing using students and medical doctors as subjects. Subjects in the medically framed experiments behave weakly and are more patient orientated in contrast to neutral framing. A sample of medical doctors exhibits comparable behavior to students with medical framing.
CRIS-Team Scopus Importer:2020-08-14
Keywords: Framing; Health economic experiment; Physician behavior; Prospective payment schemes

Short and medium-term cost effects of non-indicated thyroid diagnostics: Empirical evidence from German claims data - Hafner, Lucas; Biermann, Valeria; Donnachie, Ewan; Hueber, Susann; Kühlein, Thomas; Tauchmann, Harald; Tomandl, Johanna (European Journal of Health Economics, 2022)
This paper contributes to the discussion of whether non-indicated ultrasound examinations of the thyroid gland contribute to overtreatment and excess health care expenditures. Using two sources of claims data from Germany, we analyzed data from patients who underwent a TSH blood test which is the initial diagnostic measure to check for possible presence of thyroid dysfunction. In a matching analysis, we compared health costs of two groups of patients. One consisted of patients who underwent an early thyroid ultrasound that according to medical guidelines – at this point – was probably not indicated. The other group consisted of patients, who underwent no ultrasound examination at all or later in the course of the disease, making probable a correct indication. Both groups were made comparable by the means of a matching procedure. Average thyroid-specific health costs were substantially higher for the first group in the quarter in which the ultrasound examination took place. Some deviation in these specific costs persisted over a substantial period of time, with drug expenditures exhibiting the biggest difference. If, however, total health costs were considered, difference in costs was only found in the initial quarter. We conclude that non-indicated ultrasound examination of the thyroid gland may have some moderate effects on thyroid-specific costs. Yet the data do not suggest that long-lasting overtreatment and excess health expenditures are initiated by non-indicated ultrasound in German
Keywords: matching; health cost; non-indicated ultrasound; thyroid anomalies

Überversorgung durch nicht-indizierten Ultraschall der Schilddrüse? Eine Analyse von Routinedaten der Kassenärztlichen Vereinigung Bayerns - Hueber, Susann; Tomandl, Johanna; Hafner, Lucas; Biermann, Valeria; Tauchmann, Harald; Schöffski, Oliver; Lehmann, Maria; Schedlbauer, Angela; Gerlach, Roman; Tauscher, Martin; Donnachie, Ewan; Kühlein, Thomas (53. Kongress für Allgemeinmedizin und Familienmedizin (DEGAM), 2019)
Hintergrund Ein Ultraschallscreening auf Schilddrüsenerkrankungen bei symptomfreien Patienten gilt als möglicher Auslöser für Überversorgung, weshalb es nicht empfohlen wird. Wir vermuten, dass ein „graues“ Ultraschallscreening Kaskadeneffekte auslösen kann. Kaskadeneffekte sind definiert als eine Kette diagnostischer und therapeutischer Maßnahmen, die einmal begonnen nur schwer unterbrochen werden kann. Ziel unseres Projektes ist es, solche Kaskadeneffekte zu identifizieren und zu beschreiben. Fragestellung Welche Patienten sind von Kaskadeneffekten besonders betroffen? Gibt es Subgruppen mit unterschiedlichen Behandlungsverläufen? Wie unterscheiden sich diese Gruppen? Methoden Retrospektive Analyse eines Datensatzes der Kassenärztlichen Vereinigung Bayerns (2012 bis 2017). Untersucht werden Daten von Patienten mit nicht-indiziertem Schilddrüsen-Ultraschall, definiert als erstmaliger TSH-Test ohne die Diagnose einer Funktionsstörung, gefolgt von einem Ultraschall der Schilddrüse innerhalb von 28 Tagen. Um Subgruppen zu identifizieren wird eine Clusteranalyse nach der Häufigkeit von schilddrüsenspezifischen Untersuchungen im Zeitverlauf durchgeführt. Ergebnisse Es werden Daten von 41.065 Patienten ausgewertet. Erste Analysen lassen vermuten, dass es Subgruppen von Patienten gibt, die häufigen Kontrolluntersuchungen unterzogen werden. Die Datenanalyse ist noch nicht abgeschlossen. Vollständige Ergebnisse werden zum Kongress vorliegen. Diskussion Eine systematische Analyse und Darstellung von Überversorgungsprozessen, ausgelöst durch nicht-indizierte Untersuchungen, soll dazu beitragen, unnötige Medizin zu reduzieren. Das Projekt wird im Rahmen des BMBF-geförderten Netzwerkes PRO PRICARE durchgeführt. Take Home Message für die Praxis Die ersten Ergebnisse lassen vermuten, dass das Durchführen einer nicht indizierten Schilddrüsensonographie in bestimmen Patientengruppen zu Kaskadeneffekten und Überversorgung führen kan
Keywords: Überversorgung; Schilddrüse; Routinedaten; Versorgungsforschung